If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + 14h = 10 + 15h Solving -3 + 14h = 10 + 15h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-15h' to each side of the equation. -3 + 14h + -15h = 10 + 15h + -15h Combine like terms: 14h + -15h = -1h -3 + -1h = 10 + 15h + -15h Combine like terms: 15h + -15h = 0 -3 + -1h = 10 + 0 -3 + -1h = 10 Add '3' to each side of the equation. -3 + 3 + -1h = 10 + 3 Combine like terms: -3 + 3 = 0 0 + -1h = 10 + 3 -1h = 10 + 3 Combine like terms: 10 + 3 = 13 -1h = 13 Divide each side by '-1'. h = -13 Simplifying h = -13
| -8x=-x-3 | | 7k=9k+18 | | f(x)=140X | | 8x+8=-2+4x | | 3(2+66)=186 | | -2+5x=8x | | tgx/4=-1/2 | | 193.408x^4*729.891x^3*302.17x^2=6000 | | 3cosa-3-4sina=0 | | 688850/15 | | an=5n+3 | | (6x+9)-2(2x-5)=38 | | X^3(2x^2+4x)= | | (X+y)(dx-dy)=dy+dx | | 9x+6=6x-12 | | 9-4(5x-3)=1 | | 3cos^2x/3-3=4sinx/3 | | 3.51/4 | | 5/250=d/300 | | x+5.67y=780 | | 6+0=-2y | | kx^3=5x+2 | | lny+4x=x+3lnx | | 5x/10=13x-10 | | 35x+23y=16xy | | 36=2(v+8)-6v | | 24+3=2x+x | | 23+54-x= | | -12x-16x-3=-4(3x-2)-8x | | -2.3n+16=-5n-38 | | log-2b=3 | | 19-x=-2 |